Potentials of synthesised Lessertia montana zinc oxide nanoparticles on free radicals-mediated oxidative stress and carbohydrate-hydrolysing enzymes - Balogun, Fatai O.; Ashafa, Anoﬁ O.T. (Acta Biologica Szegediensis, 2021)
The study evaluated the effects of green absorbed zinc oxide nanostructures on oxidative stress-mediated free radicals and carbohydrate-hydrolysing enzymes. The synthesised Lessertia montana zinc oxide nanoparticles were characterised using different spectroscopic, microscopic, and diffraction techniques. The activity of L. montana ZnONPs against 1,1-diphenyl-2-picrylhydrazyl (DPPH), 2,2′-azino-bis(3-ethyl-benzothiazoline-6-sulfonic acid (ABTS), metal chelating assay, alpha-amylase and alphaglucosidase were determined using standard methods. L. montana ZnONPs were stable nanoparticles (NPs), appeared cubical (predominantly) in shape, and in nanometre range sizes. The synthesised NPs are very active (p < 0.05) against DPPH and alpha-glucosidase (0.120 and 0.037 g/L, respectively) when compared with other samples and controls, quercetin (0.349 g/L) and acarbose (0.065 g/L). However, their interaction with quercetin revealed a good ABTS (0.093 g/L) scavenging and an excellent metal chelating (0.027 g/L) effect compared to other samples. The mode of inhibition of alpha-amylase and alpha-glucosidase enzymes by L. montana ZnONPs was competitive and non-competitive, respectively. The study outcomes revealed that the synthesised ZnONPs possessed the potential to mitigate oxidative stress and diabetes in vitro.